Conceptions Of Online Teaching And Their Relationship To Teaching Approaches: A Study Of Vietnamese University Lecturers Teaching Undergraduate Distance Courses - Th.S Nguyễn Nữ Thùy Uyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Understanding teachers’ conceptions of teaching (i.e., what they believe about their teaching) is essential for improving the quality of education. As past research has shown, teachers’ approaches to teaching (i.e., how they teach) is formed by their conceptions of teaching. An insight into the relations between the two elements is also significant, as consistency between teaching conceptions and approaches could promote quality learning outcomes for students and vice versa. There has been extensive research into these topics in face-to-face teaching and some research into conceptions of and approaches to blended teaching via the Internet in on-campus courses. Nevertheless, very few studies have been conducted to examine teachers’ conceptions of and approaches to online teaching in distance education courses, despite the increasing prevalence of this form of education in higher education in recent years and in the new normal. The relationship between conceptions and approaches has also been a neglected area of research in the current literature in blended and online teaching. These are the gaps in the literature that are addressed in this thesis. This qualitative study explored the conceptions of online teaching and approaches to teaching of fourteen lecturers in a Vietnamese regional university, and assessed the extent of alignment between conceptions and approaches in their delivery of undergraduate online distance courses. Using open-ended questions, I asked what the lecturers believed about online teaching and how they taught online. Grounded theory was used to identify themes, categories and dimensions related to the participants’ conceptions of online teaching and their approaches to teaching. The categories of conceptions of online teaching for each lecturer were then compared and cross tabulated with their teaching approaches to identify matches. Document analysis was further employed where relevant to corroborate the findings. It is of note that the study commenced in 2019, with an original focus on online teaching for off-campus distance courses. However, the onset of the Covid-19 pandemic triggered a switch from on campus to off-campus online teaching in most universities in Vietnam and worldwide. Cases of the switch to online teaching during this era were included in the investigation of the project, which has led to interesting and surprising findings. The results showed that the lecturers conceived of online teaching as transmitting structured knowledge and skills, guiding students to acquire knowledge and skills, facilitating their understanding via interaction, and, developing their understanding and capabilities. These four categories of conceptions of online teaching were grouped into three major orientations: teacher-centred and student-centred orientations, and a transitional orientation labelled as a fusion of content and learning. The categories were defined by a set of six dimensions, revealing different relationships between the teacher and student, the use of e-Learning system, the content and knowledge. The descriptors of the conceptions showed cultural influences, particularly from a Confucian heritage, which is of significance as research into face-to-face conceptions had not to date found cultural variations. Lecturers’ teaching approaches were found to vary along a continuum, with two broad approaches - content-centred and learning-centred - at opposite ends. The two approaches were characterised by a one-dimensional motivation and seven-dimensional strategy framework. The lecturers taught in three different online teaching environments: video-recording, video-conferencing teaching in online distance courses, and online teaching via communication platforms during the Covid-19 era. Interestingly, the same lecturers employed different teaching approaches in the three online teaching settings. Their teaching approaches were influenced by contextual factors such as institutional policy, the nature of students, time constraints, and technological issues. The study also revealed a surprising mismatch between lecturers’ conceptions of teaching and their approaches to teaching when delivering online teaching in distance courses, whereas the alignment between the two elements was stronger in the delivery of Covid-19 online teaching. These results were unexpected, as teachers’ conceptions have been found to have a strong relationship to teaching approaches in face-to-face teaching. The underlying reasons for these inconsistencies appeared to be the influence of university policies concerning the design of distance education courses, technology, time and institutional constraints, and lecturers’ perceptions of students’ learning attitudes. The thesis has established a categorisation model for conceptions of online teaching and a framework for characterising approaches to online teaching, with clear dimensions to demarcate the elements that make up the totality of the two concepts. The fact that the study examined online teaching in both asynchronous and synchronous modes has enabled the exploration of varied dimensions of the categories of conceptions and approaches, which have set it apart from previous studies into conceptions of and approaches to other forms of teaching. The findings have extended our understanding of the relationship between conceptions of and approaches to teaching in the online environment and into the complexity of practices of online teaching and learning in Vietnamese Higher Education. Several amendments to policy and current practice are suggested to improve the quality of online teaching and learning.